Inclusive innovation in agricultural value chains: lessons from use of a systems approach in diverse settings - Horton, D.; Devaux, A.; Bernet, T.; Mayanja, S.; Ordinola, M.; Thiele, Graham (Informa UK Limited, 2023)
Systems approaches are widely promoted for inclusive innovation, but their use and results are seldom evaluated. We assessed applications of the Participatory Market Chain Approach (PMCA), which combines elements of innovation system and value chain approaches, in eight cases in Africa, Asia, Europe, and Latin America. We found that the PMCA performed best where the policy environment favoured value chain development, the chain offered significant potential for value addition, and the PMCA was implemented with high fidelity to its basic principles, and as part of a larger development effort. Facilitation was crucial for developing locally appropriate implementation procedures and engaging smallholders, commercial entrepreneurs, researchers, and other service providers throughout the PMCA application. By focusing on commercial innovation, the PMCA offered a strategic entry point for stimulating more systemic innovation. We conclude with six lessons on (1) how commercial innovation can trigger broader innovation; (2) the need to engage commercial entrepreneurs in innovation processes; (3) the importance of committed, motivated and capable facilitators; (4) the advantage of embedding the PMCA in a broader development effort; (5) how systems approaches can help R&D organizations respond better to market demands; and (6) the contributions of systems approaches to innovation capacity.